Leaf and Shoot Growth Characteristics of Abies pindrow and A. spectabilis of West Himalaya - Singh, Pradeep; Joshi, Sahil; Negi, G. C. S. (Indian Forester, 2023)
In this article leaf and shoot growth characteristics of two fir species (A. pindrow and A. spectabilis) found in the high altitude zone of Tungnath (Uttarakhand) are described with an objective to identify them easily due to their almost similar morphology. The mean height of A. pindrow trees was markedly greater than A. spectabilis (40.3Â±1.80 vs. 27.7Â±1.15 m), and the tree height declined but tree CBH increased with the increasing altitude. Both shoot diameter and number of leaves per shoot were higher in A. spectabilis for both leader (mean= 4.2 vs. 6.0 mm) and lateral shoots (mean=3.1 vs.3.88 mm). The number of leaves per shoot in A. spectabilis (mean= 146) was two and half times more that in A. pindrow (mean= 65). The leaves of A. spectabilis were comparatively smaller (length= 2.50 cm), narrower (width= 0.19 cm) and thinner (thickness= 0.25 mm) than the leaves of A. pindrow (length= 4.6 cm), narrower (width= 0.23 cm) and thinner (thickness= 0.38 mm). Leaves (needles) of A. pindrow are acute and bifid at apex, and A. specatbilis leaves are rather smooth at apex and have two greyish bands on either side of shallow mid-rib.Leaf mass (0.006 vs. 0.01 g/leaf) and leaf area 2 (0.48 vs. 1.0 cm2 /leaf) was also higher for A. pindrow. The increasing leaf thickness with altitude has important implications for understanding the ability of these two important fir species to harvest sunlight and grow in the cold environment at high altitude to devise an appropriate forest management practices in the era of climate change.